The description of Viruses according to Vibrational Herbal Medicine and the laws of Ancient Wisdom - Eltouny, Almoez LeDin Ellah M. S. (Archives of Clinical and Medical Case Reports, 2019)
The use of Vibrational Herbal Medicine as a means of study of disease and means of treatment has led us to describe what "ailment" means when describing it in vibrational terms. This has led to other descriptions for Viruses. It appears that some distinction is needed to describe a simple complex virus and another virus that needs more elucidation because its structure does not conform to the traditional description of a virus in normal circumstances. Other ailments, such as what is referred to as an Auto Immune disease, may be another type of very complex virus systems containing several main complex virus systems. The differentiation of such viruses may be done by comparing their energy characteristics to determine what type of virus it may be.